Konstytucyjne przesłanki ograniczenia wolności i praw człowieka ze względu na ochronę zdrowia publicznego w świetle doświadczeń zwalczania COVID-19 - Bernaciński, Łukasz (Ograniczenia praw i wolności wprowadzone w Polsce w związku z epidemią COVID-19: Aspekty prawne, medyczne oraz ekonomiczne, 2022)
Restrictions on human rights and freedoms enacted in connection with the fight againstCOVID-19 reminded the public that the Constitution is not a symbolic act, but a documentlaying the foundations for the functioning of the state and a guarantee of theinviolability of human freedoms and rights.Due to the fact that the fight against COVID-19 was based on the limitation of the freedomsand rights of individuals, it should be recalled which constitutional conditionsshould be met by such restrictions enacted for the protection of public health. Article31 (3) of the Polish Constitution sets out for state authorities the conditions and limitsof interference in the sphere of freedoms and rights of individuals. The former includethe requirement of the statutory form of introducing restrictions, which enforces thetransparency of the legislative process and ensures that the content of the regulation iscontrolled by the representatives of the nation sitting in the parliament. Moreover, enactingrestrictions must be related to the protection of one of the values listed in the provision,including public health. The limits of interference are determined by the principleof proportionality and the prohibition of violating the essence of freedoms and rights.The legislative activity of the COVID-19 epidemic has shown that the enacted lawraises constitutional doubts at the level of a formal premise. Enacting restrictions onfreedoms and rights in sub-statutory acts based on a questionable legal basis has ledto social unrest, undermined citizens’ trust in the state and the laws it enacted, andweakened the actual impact of legal regulations. The latter should be assessed negativelyfrom the point of view of the usefulness imperative. The implementation of therequirement of proportionality in the strict sense may also raise a number of doubts.Finally, the practice of suspending the constitutional rights of an individual can beassessed negatively. An example of such a practice may be a temporary, total ban oncertain types of economic activity or severe restrictions on the number of believerswho can participate in religious worship.